Fruit drop in two kiwifruit varieties and the use of two Bacillus-based biofungicides - Casonato, Seona (New Zealand Plant Protection, 2019)
Recently, fruit drop in two green varieties of kiwifruit (Actinidia deliciosa; VarA and VarB) has increased towards the harvest date. The efficacy of two biofungicides, applied post-flowering, to ameliorate the effects of early fruit drop in VarA and VarB during the 2017–18 growing season was tested. Treatments were applied to a single bay, with buffer bays and rows adjacent. Treatments were two different Bacillus-based biofungicide products; Serenade® Max (a.i. B. subtilis QST713 strain) and Triple-X® (a.i. B. amyloliquefaciens BS 1b). There was an untreated control. All fruits in the canopy, within the treated bay, were counted and recorded at 4-weekly intervals, over 5 months until harvest. At the VarA site, there was no statistical difference (P>0.1) in the percentage of fruit drop between the control (7%), Triple-X® (5%) and Serenade® Max (10%) treated vines. At the VarB site, fruit drop differed statistically (P<0.1) between Triple-X® treated vines (5%) and the control (10.5%), with Serenade® Max treated vines (6.5%) having intermediate fruit drop. The use of Triple-X® may be an option to assist with reducing fruit drop in kiwifruit.